2010
DOI: 10.1111/j.1365-3083.2010.02459.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Diagnosis of Tuberculosis Based on Recombinant Antigens ESAT-6 and CFP-10 in Children from an Endemic Area in Northeast Brazil

Abstract: Diagnostic tests for tuberculosis (TB) using interferon gamma (IFN‐γ) responses produced by T lymphocytes after stimulation by early secretory antigen target 6 (ESAT‐6), culture filtrate protein 10 (CFP‐10) or purified protein derivate (PPD) were carried out using ELISA (enzyme‐linked immunosorbent assay) in whole blood culture supernatants from children with suspected TB disease (n = 21), latent TB infection (LTBI; n = 17) and negative controls (NC; n = 21) from Recife, Pernambuco, Brazil. The results were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…We observed that CFP10‐induced IFNγ levels in patients with TB were of a higher magnitude than those induced by ESAT6; however, the CFP10‐induced IFNγ response did not discriminate between TB and EC groups. This corresponds with previous reports that have shown that CFP10 does not discriminate between active TB and uninfected controls [30–32]. In addition, as antigens related to ESAT6 and CFP10 are present in some NTMs that are likely to be present in this high TB endemic region, it is possible that because of cross‐reactivity to these, the discriminatory power of ESAT6 and CFP10 for identification of M. tuberculosis –infected individuals may be reduced.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We observed that CFP10‐induced IFNγ levels in patients with TB were of a higher magnitude than those induced by ESAT6; however, the CFP10‐induced IFNγ response did not discriminate between TB and EC groups. This corresponds with previous reports that have shown that CFP10 does not discriminate between active TB and uninfected controls [30–32]. In addition, as antigens related to ESAT6 and CFP10 are present in some NTMs that are likely to be present in this high TB endemic region, it is possible that because of cross‐reactivity to these, the discriminatory power of ESAT6 and CFP10 for identification of M. tuberculosis –infected individuals may be reduced.…”
Section: Discussionsupporting
confidence: 89%
“…In endemic regions, IFNγ can also be regulated by the natural exposure to M. tuberculosis or NTMs as well as BCG vaccination [34, 35]. Similar MTBs‐stimulated IFNγ responses in EC and TB could also be attributed to cross‐reactivity with MTBs in BCG‐vaccinated study subjects [29–32].…”
Section: Discussionmentioning
confidence: 99%
“…Of these antigens, a subset has been shown to be protective in animal models (Rv3619c, Rv3620c, Rv2608), highly immunogenic in humans (Rv3875, Rv3874, Rv0288, Rv1196) and strongly recognized in the initial stages of infection in humans (Rv0288 and Rv3875) [121,122]. We show that several of these antigens, including Rv3875 (ESAT-6) and Rv3874 (CFP10), which are immunodominant in humans [123–130], are also immunodominant in rhesus macaques. Our results therefore support the feasibility of evaluation in NHPs of vaccines based on these antigens.…”
Section: Discussionmentioning
confidence: 99%
“…As diferenças estatísticas entre os grupos foram avaliadas utilizando-se o teste de t Student, sendo consideradas significantes p<0,05. Centros penitenciários constituem comunidades que apresentam ambientes dinâmicos, em que os grupos de risco favorecem o desenvolvimento e a disseminação da TB (11,30). No Brasil, a população encarcerada total em 2010 era constituída por 496.251 indivíduos, e a proporção de pessoas em regime de reclusão foi de 253 por 100.000 habitantes.…”
Section: Análise Estatísticaunclassified